Contribución a la identificación de esporas del Reino Fungi en la atmósfera de La Plata, Argentina - Nitiu, Daniela Silvana (2010)
Based on the aeromycological analysis of La Plata city, artificial Morphological Groups of fungal spores were defined. This study is a methodological contribution to the identification and counting of a fraction of the atmospheric micobiota. For the definition of groups, the criteria of Saccardo (1886) were taken into account and the groupings created by Díaz et al. (1998) and Aira et al. (2005) have been reformulated. Four new groups have been created and other sporal types have been incorporated to previous classifications. Each of them includes 2 to 6 spore types belonging to the Phylum Zygomycota, Basidiomycota and Ascomycota and their anamorphs, assigned to generic level. Characters that define such associations are: Absidia Group, hyaline amerospores; Cortinarius Group, pigmented amerospores; Didymella Group, hyalines or slightly colored didymospores; Didymosphaeria Group, pigmented didymospores and didymoconidia; Leptosphaeria Group, hyaline to pigmented phragmospores and Helminthosporium Group, hyaline to pigmented distoseptated phragmoconidia. The aim of this work is to give a tool to facilitate the task of data processing by providing new qualitative elements to prior classifications and contributing to the complex problem of identification of fungal spores presents in atmosphere.